Biotechnology of Isoprenoids - Schrader, Jens; Bohlmann, Jörg (Advances in Biochemical Engineering/Biotechnology, 2015)
Albert Boronat Manuel Rodríguez-Concepción Terpenoid Biosynthesis in Prokaryotes   Claudia Schmidt-Dannert Biosynthesis of Terpenoid Natural Products in Fungi   Dorothea Tholl Biosynthesis and Biological Functions of Terpenoids in Plants   Irini Pateraki Allison Maree Heskes Björn Hamberger Cytochromes P450 for Terpene Functionalisation and Metabolic Engineering   Yun Chen Yongjin J. Zhou Verena Siewers Jens Nielsen Enabling Technologies to Advance Microbial Isoprenoid Production   Chase Kempinski Zuodong Jiang Stephen Bell Joe Chappell Metabolic Engineering of Higher Plants and Algae for Isoprenoid Production  .